Narratology, hermeneutics, and Midrash: Jewish, Christian, and Muslim narratives from the late antiquity through to modern times - Cordoni, Constanza; Langer, Gerhard (Poetik, Exegese und Narrative, 2014)
Biographical note: Constanza Cordoni ist seit 2009 wissenschaftliche Mitarbeiterin am Institut für Judaistik an der Universität Wien. Dr Gerhard Langer is professor at the Institute for Jewish Studies at the University of Vienna.